2019
DOI: 10.1590/0001-3765201920180901
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopian muscids (Diptera, Muscidae) egg-carriers of Stylogaster Macquart (Diptera, Conopidae)

Abstract: We here report for the first time on the presence of three species of the conopid genus Stylogaster Macquart (Diptera, Conopidae) in Ethiopia, viz. S. nitens Brunetti, S. westwoodi Smith and Stylogaster sp.. We further screened 908 muscid flies (Diptera, Muscidae) for the presence of impaled eggs of Stylogaster and recorded eggs on 89 individuals (9.8%). Eggs were impaled on eight species, viz. Limnophora translucida Stein, Musca lusoria Wiedemann, Musca splendens Pont, Neomyia chrysopyga (Emden), Pseudohelina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Stylogaster species target nymphs and adult Gryllidae (Orthoptera) and Blattodea, whereas other conopid genera use adult aculeate Hymenoptera (Freeman 1966;Kotrba 1997;Woodley and Judd 1998;Schmid-Hempel 2001;Rasmussen and Cameron 2004;Marshall 2012;. Stylogaster eggs have been found on other species, such as other Diptera, but the lack of egg development indicates that these may be accidental ovipositions (Couri and Barros 2010;Stuke 2012;Couri et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Stylogaster species target nymphs and adult Gryllidae (Orthoptera) and Blattodea, whereas other conopid genera use adult aculeate Hymenoptera (Freeman 1966;Kotrba 1997;Woodley and Judd 1998;Schmid-Hempel 2001;Rasmussen and Cameron 2004;Marshall 2012;. Stylogaster eggs have been found on other species, such as other Diptera, but the lack of egg development indicates that these may be accidental ovipositions (Couri and Barros 2010;Stuke 2012;Couri et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is further supported by records of larvae inside attached eggs, placed with their head towards the blunt micropylar end of the egg (Fig. 3D, Smith and Cunningham-Van Someren 1985, Couri et al 2013), and Stuckenberg (1963 found an empty egg attached to Dichaetomyia quadrata (Wiedemann) with the micropylar end "irregularly broken open" and interpreted this as a hatched egg. If the larva hatches from the egg through the end facing away from the host, especially for eggs that are attached to the ventral part of the host, it would appear that there is a high risk that the emerging larva would fall off the host.…”
Section: Larval Biologymentioning
confidence: 66%
“…Therefore, there is no firm evidence that these flies are regular or occasional hosts or even if they are hosts at all. It has been speculated that the calyptrate flies instead are used to transport the eggs to the final host or food source or that the flies just happen to share the same appearance or habitat as the host of Stylogaster and, therefore, accidentally become impaled with eggs (Smith 1967, Ferrar 1987, Couri and Pont 2006, Couri and Barros 2010, Stuke 2012, Couri et al 2013), but the evidence to support this remains circumstantial.…”
Section: Stylogaster Egg-carriersmentioning
confidence: 99%
See 2 more Smart Citations